Positivisasi Syariat Islam di Aceh - Myaskur; Nurul Syalafiyah (Asy-Syari’ah : Jurnal Hukum Islam, 2021)
Al-Qur'an and Sunnah as the revealed law is the main basis of Islam is to bring mercy to all natural and has become a lifeline beliefs and muslims especially the people of Aceh. Interpretation of Islamic Sharia through fiqh, which manifested in a kanun be sustained by engaging all community stakeholders. The formation, implementation, and enforcement of kanun in all areas of life (kaffah) performed fairly against any person who violated the undiscriminating social structure. Kanun improvements to address the growing state of society as a whole is done with due respect to the substance, structure, and culture (adat) communities. The values ​​of the benefit, harmony, and avoid kemudharatan should ensoul of siyasah syar'iyyah that the principle of purposiveness pensyariatan (al-maqashid al-syar'iyyah) and the principle of policy and laws (al-tasyri wisdom).